PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM PENINGKATAN AKSES MASYARAKAT TERHADAP PENDIDIKAN YANG BERKUALITAS DIJEMBATANI DENGAN MANAJEMEN SUMBER DAYA MANUSIA - NURHAPANI NURHAPANI (Ensiklopedia Education Review, 2019)
Education is one of the most important pillars in improving human quality, even educational performance, which is a combination of gross enrollment rates (APK) for basic education up to tertiary education and literacy rates is used as a variable in calculating the Human Development Index (HDI) together with health and economic variables. Therefore the development of national education must be able to guarantee equal opportunities for education, improve quality and the relevance and efficiency of education management to face challenges in accordance with the demands of changes in local, national and global life. The development of national education to be carried out in the period 20014 - 20019 has considered international agreements such as Education For All, Convention on the right of child and Millennium Development Goals (MDGs) and World Summit on Sustainable Development which clearly emphasizes the importance of education as a way to reduce poverty, improve justice and gender equality, understanding cultural values and multiculturalism, as well as increasing social justice. Keywords: Human Resource Management, Education, Society, Quality.